Regional Differentiation of Human Potential Indicators - Lokosov, Vyacheslav Veniaminovich; Ryumina, Yelena Viktorovna; Ulyanov, Vladimir Vasilyevich (Economy of Regions, 2015)
We purpose of the article is the interregional analysis of human potential. In comparison with the quality of life of the population, the quality of population itself is studied far less. The article presents an expanded characteristic of human potential in seven directions: economic activity, demographic processes, physical health, cultural potential, social health, educational potential and the attitude of the population to the environment. On the basis of statistics for 2008-2012 years, 63 indicators of human potential for all directions are selected. In the final result, the correlation analysis has led to the substantiation of the system of indicators consisting of 10 indicators. Three economic and seven social indicators characterizing human potential are included into this system. On the basis of the indicators by means of hierarchical agglomerative methods of cluster analysis, a classification of the Russian regions is carried out in two versions: with economic indicators and without them. The result of the calculations is a stable temporal typology of regions by indicators of human potential covering 74.4 % of the population of Russia. We article provides a substantial interpretation of dividing regions into groups, identifies the strengths and weaknesses of each cluster, shows the specific features of the regions included into the clusters. We obtained results can be used in the development of measures for the reduction of the interregional inequality in terms of human potential. It is possible to define what measures can be effective by studying the strategic directions of the development of regions in the cluster which is the most successful regarding the characteristics of human potential.